Annual report readability and corporate agency costs - Jin-hui Luo; Xue Li; Huayang Chen (China Journal of Accounting Research, 2018)
Annual reports are the main sources of information for outside investors' investment decisions and enable shareholders to supervise the management. Difficulties with the readability of these reports may therefore have serious consequences. Using 19,221 firm-year observations of Chinese A-share listed firms from 2001 to 2015, we investigate the association between annual report readability and corporate agency costs, where readability is proxied by report file length and/or file size. We find that firms with better annual report readability experience lower agency costs, and the negative association between readability and agency costs is more pronounced in firms with higher external audit quality, internal control quality or analyst coverage. These results hold after several robustness checks. The positive effect of annual report readability is stronger in private firms than in state-owned enterprises, and becomes stronger after the implementation of new accounting standards in 2007. Readable annual reports can help in monitoring corporate insiders opportunistic behavior and thus reduce agency costs.
Keywords: G32; G34; 650; Annual report readability; Agency costs; External audit quality; Internal control quality; Security analysts